Animasi Interaktif Klasifikasi Jangkauan Dan Topologi Jaringan Komputer Berbasis Android Sebagai Media Belajar - Muhammad Rezki; Muhammad Ifan Rifani Ihsan; Diah Ayu Ambarsari (Computer Science (CO-SCIENCE), 2021)
Classification of range and topology has its own types and characteristics. There are many types of outreach classifications and topologies, as well as process methods in learning in schools that are less interactive so that students are bored in the learning process, especially for students of SMK Computer and Network Engineering Department. In practice, making LAN cables requires equipment that is quite expensive, making it difficult to carry out these practical activities outside of school. So that students find it difficult to develop their abilities, especially in the vocational field. With current technological developments, of course, it can be used in the world of education, one of the uses is by making educational applications that can provide a new atmosphere in learning. Interactive animation can be a solution in overcoming the practice of making LAN cables and an explanation of Network Topology. This interactive animation was made using Construct 2 software, developed using multimedia development methods and data collection techniques in the form of observations, interviews and literature studies. The purpose of making interactive applications is so that students can understand the range classification and topology well, and can practice installing LAN cables through interactive animation simulation software as a substitute for school facilities.